Frozen Blood Products: Clinically Effective and Potentially Ideal for Remote Australia. Issue 1 (January 2013) - Holley, A.; Marks, D. C.; Johnson, L.; Reade, M. C.; Badloe, J. F.; Noorman, F.
The development of effective cryopreservation techniques for both red blood cells and platelets, which maintain ex vivo biological activity, in combination with frozen plasma, provides for a unique blood banking strategy. This technology greatly enhances the storage life of these products. The rationale and potential advantages of using cryopreservation techniques for the provision of blood products to remote and military environments have been effectively demonstrated in several conflicts over the last decade. Current haemostatic resuscitation doctrine for the exsanguinating patient supports the use of red blood cells, platelets and frozen plasma early in the resuscitation. We believe an integrated fresh–frozen blood bank inventory could facilitate provision of blood products, not only in the military setting but also in regional Australia, by overcoming many logistic and geographical challenges. The processes involved in production and point of care thawing are sufficiently well developed and achievable to make this technology a viable option. The potential limitations of cryopreservation and subsequent product thawing need to be considered if such a strategy is to be developed. A substantial body of international experience using cryopreserved products in remote settings has already been accrued. This experience provides a template for the possible creation of an Australian integrated fresh–frozen blood bank inventory that could conceivably enhance the care of patients in both regional Australia and in the military setting.